2020
DOI: 10.1037/adb0000530
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational marijuana use: A life course examination of the relationship between parental trajectories of marijuana use and the onset of marijuana use by offspring.

Abstract: Prior research documents intergenerational (IG) continuity in marijuana use, with most work adopting a life course perspective. Incorporating a methodology that allows for the measurement of "patterns of behavior" instead of singular aspects of parent marijuana use (e.g., age of onset or frequency at any one age or ages), we investigated the simultaneous effects of parental age of onset, frequency, and duration of marijuana use across 3 periods of the life course (i.e., adolescence, emerging adulthood, and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…In contrast to other family dysfunctions, studies have mainly yielded mixed results regarding household substance abuse and intergenerational transmission (Langevin et al, 2019). The studies showing a positive link between the two variables showed that children whose parents consume illegal substances were more likely to also use drugs (Augustyn et al, 2020;Kerr et al, 2020). In some studies, this negative effect was even present across three generations (Neppl et al, 2020;Tiberio et al, 2020).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
“…In contrast to other family dysfunctions, studies have mainly yielded mixed results regarding household substance abuse and intergenerational transmission (Langevin et al, 2019). The studies showing a positive link between the two variables showed that children whose parents consume illegal substances were more likely to also use drugs (Augustyn et al, 2020;Kerr et al, 2020). In some studies, this negative effect was even present across three generations (Neppl et al, 2020;Tiberio et al, 2020).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
“…Bears Augustyn et al (2020) found that offspring of parents who initiated marijuana use early and escalated use over time (chronic use) had an increased likelihood of onset of marijuana use during adolescence. The same was true for children of parents who started using marijuana late in adolescence and persisted with moderate use in adulthood.…”
Section: Key Study Findingsmentioning
confidence: 99%
“…Epstein et al (2020) found that children of early-onset substance use parents were a high-risk group for initiating their own substance use early in life, while Tiberio et al (2020) found that marijuana use versus no use, but not parents’ age of first use during adolescence, was predictive of children’s future marijuana use. Last, but not least, the Bears Augustyn et al (2020) study revealed that parents’ age of onset was important in a counterintuitive manner: Children of parents who started marijuana use in early adolescence and persisted moderate use through adulthood presented the lowest risk of initiating their own use. By the same token, children of late-onset parents whose use also persisted in a moderate manner through adulthood presented the highest onset risk profile.…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies vary with respect to how different aspects (e.g., age of onset) and trajectories of parental substance use (e.g., early-onset persistent vs. late-onset persistent) are related to child substance use as well as how use of specific drugs in one generation is associated with the use of specific drugs in the next generation (e.g., cannabis in G1 to cannabis, alcohol, and/or tobacco in G2). Bears Augustyn, Loughran, Larroulet, Fulco, and Henry (2020) note the value of looking at patterns or full trajectories of parent use across life periods, rather than a singular aspect of parent cannabis use (e.g., age of onset) to fully uncover associations with offspring use. Findings by Tiberio, Kerr, Bailey, Henry, and Capaldi (2020) also suggest the importance of examining patterns beyond a singular variable.…”
mentioning
confidence: 99%